Complexities of Implementation: Oxfam Australia's Experience in Piloting Blockchain - Hallwright, Joshua; Carnaby, Elsa (Frontiers in Blockchain, 2019)
This paper describes one of Oxfam's pilot projects exploring blockchain technology, focusing on the non-technological, institutional challenges faced by the organization. There is an emerging literature on blockchain for social good, however, this predominantly focuses on the use cases and issues relating to applying the technology in international development projects. A gap in the literature exists regarding the non-technological aspects of blockchain projects both within the sector and more broadly. Addressing this gap is critically important as many of the promises of blockchain technology will only eventuate in their fullest when whole ecosystems are using the technology. To get there requires a transition period and it is this transition period that holds the key to success for organizations exploring the technology. This paper goes some way to addressing this gap. It does so by describing a specific case study and unpacking some of the organizational challenges associated with implementing a blockchain-based project in the international development and humanitarian sector. This has important implications for the sector as blockchain technology becomes ever more present as a tool capable of reducing inequality and addressing power imbalances. The Oxfam case study described in this paper highlights the difficulty many not-for-profits are having engaging with the technology. The lessons are drawn from a specific use case of a current pilot project using blockchain technology in a cash transfer preparedness project in a small island developing state. Although important and insightful, this paper does not focus on the specifics of the application of the technology but rather discusses the myriad non-technological challenges faced from Oxfam Australia's perspective. These are categorized into three main areas: awareness and understanding of the technology, capacity constraints of in-house support services in providing relevant support for a nascent technology, and issues related to engaging in non-traditional partnerships. The paper concludes by recommending further areas of research and suggestions to develop practical tools and guidance to help the international development and humanitarian sector navigate this emerging technology.